Guidelines for the assessment and planning of estuarine barrages - Burt, Neville; Rees, Andy, 1960- (Thomas Telford, 2001)
Based on research commissioned by DETR and the Environment Agency, 'Guidelines for the Assessment and Planning of Estuarine Barrages' presents guidance on the planning, design, construction and operation of estuarine barrages.